Diet diversity during pregnancy and infant growth outcomes in Uganda. - Madzorera, Isabel. (Tufts University. Tisch Library., 2019)
This presentation was from Annual Partners meeting in Boston.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy